Antibacterial and cytotoxic properties of boron-containing dental composite - (:unkn) unknown (My University, 2015)
0

Secondary dental caries are one of the major reasons for restoration replacements. Incorporating antimicrobial properties into dental materials would limit the initiation and progression of dental caries. In the current study, dental composites having 1%, 5%, and 10% (w/w) sodium pentaborate pentahydrate were prepared and analyzed for their mechanical properties, degree of monomer conversion (DC) rate, antibacterial efects against Streptococcus mutans, and biocompatibility with human dental pulp stem cells (hDPSCs). Incorporation of boron into the composites signifcantly decreased fexural strength and DC in a dose-dependent manner, but the value for 1% boron-containing composite still remained within acceptable levels. Compressive strength and diametral tensile strength were not found to be diferent from those of controls. Although no inhibition zone was detected in an agar-well difusion assay for any materials tested, signifcant bacterial growth inhibition was obtained in a direct contact test for boron-containing composites. Immunocytochemical and lineage-specifc gene expression analysis revealed that composites with boron content increased the osteogenic and odontogenic capacity of hDPSCs. Boron-containing dental composites showed promising results for future clinical applications, displaying nontoxic, osteogenic, and odontogenic-inducing characteristics with remarkable antibacterial activity against S. mutans, and are hence potentially able to prevent secondary caries.
Keywords: Biyoloji